2006
DOI: 10.1177/1043659606291550
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptation of Mothers of Children With Intellectual Disability in Lebanon

Abstract: In many Middle Eastern countries, including Lebanon, there is a stigma attached to families who have an intellectually impaired child. These families complain of isolation and lack of community resources that could help them cope with their circumstances to optimize the child's abilities. Health professionals and researchers should be cognizant of factors related to the process of stress adaptation to help families cope with their circumstances. The aim of this cross-sectional study was to identify factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 24 publications
4
21
0
2
Order By: Relevance
“…One-fourth of the 20 studies in this group identified a theoretical orientation. Fifteen percent [Lustig and Akey, 1999;Van Riper, 2000;Azar and Badr, 2006] cited a theory related to the work of McCubbin and coworkers McCubbin and McCubbin, 1993;McCubbin et al, 1996]. These articles all had theoretical inconsistencies among terminology, definitions, and theory.…”
Section: Conceptualizing and Measuring Outcomesmentioning
confidence: 93%
“…One-fourth of the 20 studies in this group identified a theoretical orientation. Fifteen percent [Lustig and Akey, 1999;Van Riper, 2000;Azar and Badr, 2006] cited a theory related to the work of McCubbin and coworkers McCubbin and McCubbin, 1993;McCubbin et al, 1996]. These articles all had theoretical inconsistencies among terminology, definitions, and theory.…”
Section: Conceptualizing and Measuring Outcomesmentioning
confidence: 93%
“…The authors suggested that simply having a large social support network is insufficient to improve the wellbeing of mothers in the absence of ASD-specific formal supports. Azar and Badr (2006) attributed the high levels of stress and depression observed among mothers of children with intellectual disabilities in Lebanon to stigma associated with disability and to financial burdens associated with caring for their children. Indeed, surveys examining attitudes towards people with disabilities among community members in Jordan and college students in Lebanon revealed negative attitudes towards people with disabilities (Nagata 2008).…”
Section: Knowledge Of Asd In Lebanonmentioning
confidence: 96%
“…Other studies have shown that the stress levels of mothers of children with ASD are higher than those of mothers of nonAlthough cross-cultural similarities exist related to stress in caring for a child with disabilities [6,7], individual and cultural differences play a critical role in how parents respond and cope with the challenges related to their child [8]. Relatively little is known about the coping behaviors of Middle Eastern mothers, and there is only one published study on fathers [9].…”
Section: Ways Of Coping Mental Burnoutmentioning
confidence: 99%